Strategies for achieving successful cannulation in endoscopic retrograde cholangiopancreatography: A technical overview - Ismail, Alaa; Abdelwahab, Maya M.; Ozercan, Mubin; Elnahas, Osama; Bahcecioglu, Ibrahim H.; Yalniz, Mehmet; Tawheed, Ahmed (Baishideng Publishing Group Inc, 2025)
Endoscopic retrograde cholangiopancreatography (ERCP) is a vital diagnostic and therapeutic technique in evaluating and treating biliary and pancreatic disorders. Since its inception in the late 20(th) century, ERCP has transitioned from a mostly diagnostic instrument to a chiefly interventional procedure, owing to the emergence of less invasive imaging techniques like magnetic resonance cholangiopancreatography and endoscopic ultrasonography. Successful biliary cannulation is the most important and difficult step of the procedure. However, there are many challenges associated with cannulation, such as the anatomy of the major duodenal papilla, the direction of the common bile duct and pancreatic duct in the ampulla of Vater, the presence of periampullary diverticula, and scope position. Advanced techniques for cannulation are necessary when basic techniques fail. Double guidewire, precut methods, and transpancreatic sphincterotomy are examples of these advanced techniques. This review aims to summarize the challenges of biliary cannulation and tips for performing cannulation techniques.
Keywords: Biliary diseases; Cannulation; Common bile duct; Endoscopic retrograde cholangiopancreatography; Sphincterotomy; Needle knife; Pancreatic duct